Sala de leitura como espaço de resistência : práxis bibliotecária em Cachoeiro de Itapemirim-ES - Gomes, Laís Lupim Santos (2024)
It is understood that school libraries are not mere complements, but fundamental elements of the pedagogical environment, whose presence is vital in the daily life of schools. However, achieving the universalization of these spaces has faced a series of practical challenges, with the shortage of properly qualified librarians being one of the main obstacles nationwide. These difficulties compromise the effectiveness of policies aiming to universalize school libraries, making it crucial to seek solutions to overcome these barriers. In this context, this study investigates the socio-educational role of reading rooms in municipal schools of Cachoeiro de Itapemirim/ES, as well as explores how librarians can contribute to managing these spaces, using librarian praxis as a central approach. The study diagnoses the current situation of the reading rooms, analyzes the actions taken, the professionals involved, the physical environment, management, and existing policies. It also examines the integration and participation of librarians in these rooms, comparing them with school libraries, and discusses how librarian praxis can be a differential in managing these spaces. To achieve these objectives, a mixed methodological approach is adopted, combining exploratory and descriptive elements. The research includes an initial literature and document review, followed by a mixed data collection to understand the dynamics of reading rooms in Cachoeiro de Itapemirim. Finally, a Case Study method is used to analyze the data obtained and formulate recommendations. Based on this knowledge, projects for reading rooms managed by librarians are suggested as a viable alternative to address the lack of qualified professionals. The results highlight the reading room as a sociocultural device and information center, emphasizing the importance of their management by qualified librarians. Furthermore, it underscores the value of librarian praxis for the development of reading rooms, with an emphasis on their sociocultural and critical dimensions